2021
DOI: 10.4103/jpn.jpn_61_20
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-radiological correlation with outcome in traumatic pediatric extradural hematoma: A single institutional experience

Abstract: A BSTRACT Background: Head injury is one of the leading causes of mortality and morbidity in the developing as well as developed countries. Extradural hematoma is seen in 1–2% of cases of head injury patients. Extradural hematoma is infrequent in the pediatric age group (less than 18 years) as duramater is tightly adherent to the inner table of the skull and is present in about 1–3% of all pediatric head injuries. Materials and Methods: The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
3
2
1
Order By: Relevance
“…There was a higher incidence of EDH in males than females, which is consistent with other studies 13 15 . The male preponderance may be attributed to the early riding of unsupervised two-wheelers and more physical and outdoor sports activities than girls 16 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…There was a higher incidence of EDH in males than females, which is consistent with other studies 13 15 . The male preponderance may be attributed to the early riding of unsupervised two-wheelers and more physical and outdoor sports activities than girls 16 .…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our study, the study by Jamieson and colleagues and Sobti and colleagues also showed loss of consciousness as a most common presentation 15 , 24 . 44.9% of patients presented with loss of consciousness, and there was a statistically significant difference when correlated with the number of days in the hospital.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The literature reports GCS at the time of presentation, age, associated intradural lesions as well as time between evacuation of hematoma because of transfer of the affected individual to neurosurgery unit as some of the most significant factors influencing outcomes among such patients. [9][10][11][12] Rehman L et al following patients of acute traumatic extradural hematoma for duration of 3 months revealed that 24 (80.0%) cases had had good outcome, one (3.33%) had moderate disability (left sided weakness), one (3.33%) remained in vegetative state, while mortality was noted in 3 (10.0%) cases. Rehman L et al also observed that patients who had GCS scores between 13-15 had significantly better otucomes (p=0.01) while mortality was significantly among patients who had GCS scores between 3-8 (p=0.01).…”
Section: Discussionmentioning
confidence: 99%